MORPHOLOGICAL AND THERMAL PROPERTIES OF ALKALI TERATED BACTERIAL CELLULOSE FROM COCONUT WATER - Lucia Indrarti; Rike Yudianti (Jurnal Sains Materi Indonesia, 2012)
MORPHOLOGICAL AND THERMAL PROPERTIES OF ALKALI TERATED BACTERIAL CELLULOSE FROM COCONUT WATER. Alkali treatment is one ofwide chemical treatment for removing non cellulosic materials and other impurities of bacterial cellulose (BC). Presently, BC produced by synthetic medium such as Schramm Hestrin or coconut water fermentation using pure culture of Acetobacter xylinum . In this research BC produced from coconut water fermentation using inoculums as suspension of mixture culture of bacteria A. xylinum in coconut water which commercialised inWest Java (Cianjur). Purpose of this research is to know the native and the effect of alkali treatment on the BC (heterofermentive) with evaluation of morphological, elemental analysis and thermal properties by Scanning ElectronMicroscope (SEM)-Energy Dispersive X-ray Spectroscopy (EDX) and Thermo-Gravimetry Analysis (TGA), respectively. Observation on morphological surface of native BC showes that there were noncellulosic materials entangled on the network of cellulose fibrils whichwere identified by EDX analysis as sodium(Na),magnesium(Mg), aluminium (Al), silica (Si) and potassium (K) in addition to carbon (C) and oxygen(O). On thermal analysis, stepwise of decomposition are observed on the native BC indicating the presence of non-cellulosic components which decomposed at different temperatures.While the alkali- treated BC sheet shows a single decomposition stage. The amount of residue formed after alkali treatment was relatively lower than native BC. Thermal degradation properties of the BC produced from coconut water was higher than that of BC belonging to synthetic medium. Based on this data, it is concluded that alkali treated cellulose can be used as a reasonable substitute for various non biodegradable synthetic polymers for large scale industrial in specific application